2016
DOI: 10.1371/journal.pone.0160634
|View full text |Cite
|
Sign up to set email alerts
|

Renal Denervation Suppresses the Inducibility of Atrial Fibrillation in a Rabbit Model for Atrial Fibrosis

Abstract: Renal denervation (RD) was reported to reduce the susceptibility of atrial fibrillation (AF), but the underlying mechanism has not been well understood. This study was performed to investigate the effect of RD on the inducibility of AF in a rabbit model for atrial fibrosis and to explore the potential mechanisms. Thirty-five rabbits were randomly assigned into sham-operated group (n = 12), abdominal aortic constriction (AAC) group (n = 12) and AAC with RD (AAC-RD) group (n = 11). The incidence of AF induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…[36][37][38] Our previous study clearly indicated that permanent ventricular pressure overload by AAC induces atrial remodelling, including hypertrophy, dilatation and fibrosis, and susceptibility to AF. 39 This is consistent with other observations that AAC induced atrial fibrosis and increased vulnerability to AF. 28,40 Atrial interstitial fibrosis provides a better understanding of the initiation, maintenance and progression of AF.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…[36][37][38] Our previous study clearly indicated that permanent ventricular pressure overload by AAC induces atrial remodelling, including hypertrophy, dilatation and fibrosis, and susceptibility to AF. 39 This is consistent with other observations that AAC induced atrial fibrosis and increased vulnerability to AF. 28,40 Atrial interstitial fibrosis provides a better understanding of the initiation, maintenance and progression of AF.…”
Section: Discussionsupporting
confidence: 93%
“…As a result, atrial non‐homogeneity in conduction contributes to the maintenance and progression of AF . Our previous study clearly indicated that permanent ventricular pressure overload by AAC induces atrial remodelling, including hypertrophy, dilatation and fibrosis, and susceptibility to AF . This is consistent with other observations that AAC induced atrial fibrosis and increased vulnerability to AF .…”
Section: Discussionsupporting
confidence: 89%
“…A number of experimental studies investigated the mechanism underlying the potential antiarrhythmic effects of RDN. As summarized in Table , these basic studies demonstrated that, beyond BP reduction, RDN can prevent atrial electrophysiological changes, reverse atrial electrical and structural remodeling further reduce AF inducibility and AF episodes via modulating renal sympathetic nervous activity . The favorable antiarrhythmic effects independent of BP lowering were also observed at human research level .…”
Section: Discussionmentioning
confidence: 83%
“…As summarized in Table 6, these basic studies demonstrated that, beyond BP reduction, RDN can prevent atrial electrophysiological changes, reverse atrial electrical and structural remodeling further reduce AF inducibility and AF episodes via modulating renal sympathetic nervous activity. [36][37][38][39][40][41][42][43][44][45][46][47][48][49] The favorable antiarrhythmic effects independent of BP lowering were also observed at human research level. 50 Collectively, these mechanism investigations provide in-depth and rational explanations for the positive clinical outcome of the present study.…”
Section: Adjunctive Role Of Rdn In Af-experimental Investigationsmentioning
confidence: 81%
“…53 In animals, RDN decreased the inducibility of AF. 54 In humans, Pokushalov et al 55 compared pulmonary vein isolation (PVI) alone and in combination with RDN in a small cohort (n = 27) of hypertensive patients with AF. The addition of RDN decreased AF episodes compared with PVI alone (69% vs. 29%, P = 0.033).…”
Section: Renal Denervation For Hf and Arrhythmiasmentioning
confidence: 99%